2015
DOI: 10.1007/s00213-015-4055-2
|View full text |Cite
|
Sign up to set email alerts
|

Distraction produces over-additive increases in the degree to which alcohol impairs driving performance

Abstract: Rationale Research indicates that alcohol intoxication and increased demands on drivers’ attention from distractions (e.g. passengers and cell phones) contribute to poor driving performance and increased rates of traffic accidents and fatalities. Objectives The present study examined the separate and combined effects of alcohol and distraction on simulated driving performance at blood alcohol concentrations (BrACs) below the legal driving limit in the United States (i.e. 0.08%). Methods Fifty healthy adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…It is recognized that this situation is somewhat simplistic given that everyday driving also requires individuals to simultaneously contend with a multitude of distractions, such as numerous dashboard controls, passengers in the vehicle, and cellular telephones. Laboratory research has shown these forms of distraction impair driving skill, especially in drivers under the influence of alcohol (e.g., Harrison and Fillmore, 2011; Rakauskas et al, 2008; Van Dyke and Fillmore, 2015). At present it is unclear how such distracting or high demand driving environments might affect drivers’ proclivity for risk-taking, and the degree to which alcohol might increase such risky driving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognized that this situation is somewhat simplistic given that everyday driving also requires individuals to simultaneously contend with a multitude of distractions, such as numerous dashboard controls, passengers in the vehicle, and cellular telephones. Laboratory research has shown these forms of distraction impair driving skill, especially in drivers under the influence of alcohol (e.g., Harrison and Fillmore, 2011; Rakauskas et al, 2008; Van Dyke and Fillmore, 2015). At present it is unclear how such distracting or high demand driving environments might affect drivers’ proclivity for risk-taking, and the degree to which alcohol might increase such risky driving.…”
Section: Discussionmentioning
confidence: 99%
“…Drivers were penalized $0.50 for each crash. This response conflict scenario is designed to mimic everyday driving behaviors in which drivers are rewarded by arriving at their destination on time at the cost of potential traffic citations, and has been successfully used in other research in our laboratory (e.g., Van Dyke and Fillmore, 2015; Fillmore et al, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…For instance, our simulator protocol lacked distractors common in typical driving contexts including passengers, radio, phone calls, and texting. Performance of younger drivers under distractor conditions has been demonstrated to be particularly susceptible to disruption by moderate alcohol doses (Harrison and Fillmore, ; Van Dyke and Fillmore, ). A simulation containing such distraction might alter the observed patterns of neural alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Where research has considered both performance and risky driving in the same study, driving skill appears to be impaired and risk-taking elevated following alcohol consumption, compared to a placebo beverage (Laude & Fillmore, 2015;Van Dyke & Fillmore, 2015). Further highlighting this distinction, other work (Berthelon & Gineyt, 2014; E. L. R. Harrison & Fillmore, 2011;Veldstra et al, 2012) has revealed an effect of alcohol only on driving skill, and not risky driving.…”
Section: Whisky To Riskymentioning
confidence: 97%
“…As such, participants may consider running a red light to be appealing, yet by doing so participants run the risk of a collision which would cost more time (Chein, Albert, O'Brien, Uckert, & Steinberg, 2011). Moreover, in previous studies (e.g., E. L. R. Harrison & Fillmore, 2011;Laude & Fillmore, 2016;Van Dyke & Fillmore, 2015) a clear distinction is made between measurement of impaired driving skills (e.g., lane deviation) and risky or reckless driving (e.g., driving through a red light). This suggests that the contribution of alcohol towards drink-driving-related incidents is complex, as intoxication affects multiple associated behaviours (e.g., driving skill, motor coordination and risk-taking behaviour).…”
Section: Whisky To Riskymentioning
confidence: 99%